Evaluation of Periodicals Journals and Community of Medical Sciences in Iran - A Najari; SJ M. Ghazisaid; NR Ghorbani; RN Heidari (Tehran University of Medical Sciences, 2010)
"nBackground: Medical journals are scientific resources where utilization of knowledge is availed and create an environment of competitiveness. To speed up the growth and increase scientific production and in order that the rank of Iranian journals be defined regionally and globally, journal standardization is necessary. This study was done to evaluate the country's medical journals from 2004-2006. "nMethods: This is a descriptive/analytical study. Evaluation was based on the following; scientific credibility, registry and year of service, journal management, technical quality and accessibility. The number of journals evaluated during 2004-2006 were 86, 103 and 93, respectively and the process involved 3 phases 1) defining the journal's structural indicators and designing the evaluation form 2) collection, sharing and final confirmation of information with the publication staff 3) data entry, analysis and ranking"nResults: Improvement and growth of publication depends largely on 5 parameters and its development were based on the following; publication management (61.62 points), scientific credibility (43.80 points), quality of accessing the journals (37.05 points), quality of publication (14.80 points) and registry and year of service (0.02 points). Based on the study, an upward developmental trend of the country's medical journals can be seen and the tools were sufficient in terms of validity and reliability. A revised and more comprehensive checklist that would evaluate all aspects of a publication basing on latest indicators is developed. "nConclusion: Evaluations of the country's medical journals not only promote compliance to international standards but also led to more indexing of journals in accredited international indices.